2021
DOI: 10.1038/s41467-020-20766-0
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 regulates mast cell identity and responsiveness to antigenic stimulation by promoting chromatin remodeling at super-enhancers

Abstract: Mast cells are critical effectors of allergic inflammation and protection against parasitic infections. We previously demonstrated that transcription factors GATA2 and MITF are the mast cell lineage-determining factors. However, it is unclear whether these lineage-determining factors regulate chromatin accessibility at mast cell enhancer regions. In this study, we demonstrate that GATA2 promotes chromatin accessibility at the super-enhancers of mast cell identity genes and primes both typical and super-enhance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 75 publications
1
38
0
Order By: Relevance
“…AP1 activity is positively associated with the development of IgE-mediated allergic diseases, and AP1 inhibition can suppress allergic asthma symptoms [ 43 46 ]. To examine the allergenic role of AP1, we employed T-5224, a selective c-Fos/AP1 inhibitor produced by Aikawa et al based on the crystal structure of the AP1-DNA complex [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…AP1 activity is positively associated with the development of IgE-mediated allergic diseases, and AP1 inhibition can suppress allergic asthma symptoms [ 43 46 ]. To examine the allergenic role of AP1, we employed T-5224, a selective c-Fos/AP1 inhibitor produced by Aikawa et al based on the crystal structure of the AP1-DNA complex [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…To identify potential machineries involved in allowing transcription of antisense of FCER1A, we analyzed gene configuration of FCER1A locus in FcεRIα-expressing bone marrow derived mast cells using NCBI Gene Expression Omnibus (GEO) datasets (GSE145542 and GSE145544)(Li et al, 2021). We found that binding signals for H3K4me3 and H3K27ac, two histone modification fashions with upregulating activities on gene transcription, are enriched at not only at 5’promoter regions of FCER1A- S as expected but also at putative 5’promoter flanking region of FCER1A- AS in BMMC with comparable peak levels (Fig 7a).…”
Section: Resultsmentioning
confidence: 99%
“…A series of studies have shown that eRNA expression and enhancer activity precede transcriptional induction of inflammatory genes in response to LPS [39][40][41]. More recently, tamoxifen-induced ablation of lineage-determining transcription factor GATA2 has revealed that GATA2 regulates mast cell identity and responsiveness to antigenic stimulation by promoting chromatin remodeling at SEs [42]. Interestingly, in mouse primary B lymphocytes upon B-cell receptor activation, a mathematical modeling revealed that higher fold change of mRNA induction is associated with DNA length of SE while threshold response (i.e., switchlike) response is predefined by the coexistence of PU.1 and nuclear factor (NF)-jB in the SE [43].…”
Section: Ses In Immune Cells and Nonimmune Cellsmentioning
confidence: 99%